Maternal Dengue and Health Outcomes of Children - Martin Foureaux Koppensteiner; Livia Menezes (Institute of Labor Economics (IZA), 2022)
We study the effect of maternal dengue infections on birth outcomes using linked administrative records from Brazil estimating maternal fixed-effect specifications. In contrast to previous studies, we find robust evidence for the negative effect of dengue infections on birth weight (BW). The effect is particularly pronounced at lower parts of the BW distribution, with an increase of 15%, 67%, and 133% for low, very low, and extremely low BW, respectively. Maternal dengue also has negative health consequences beyond birth outcomes; we document large increases in children's hospitalisations and medical expenditures for up to three years after birth.
Keywords: I15; I18; J13; 330; maternal dengue; birth outcomes; children hospitalisations